Eksistensi Lembaga Pengumuman Terhadap Legalitas Sertipikat Hak Atas Tanah (Pelaksanaan Pendaftaran Tanah Sistematik Lengkap) - Mitta Ramadany Wael; Sarjita Sarjita; Mujiati Mujiati (Tunas Agraria, 2019)
Abstract: The implementation of the announcement agency in land registration to apply the principle of publicity, but in its implementation according to PP 24 of 1997 and the PTSL regulation there is a difference in both the number of days of implementation and the status of registered parcels. This research used legal research methods is a normative law research methods and empirical juridical law that aims to determine the existence of the announcement agency in the implementation of PTSL and find out the legal consequences of the announcement agency on the legality of the Land Rights Certificate. The result of this research is the existence of the announcement agency in PP No. 24 of 1997 is different from the implementation of PTSL. Explicitly in PP No. 24 of 1997 the announcement was only carried out for customary land for 30 days and the announcement of state land was not implemented while the existence of the announcement agency in PTSL did not differentiate the status of the land, either state land or customary land, the announcement was still held for 14 calendar days. In accordance with the hierarchy of state the Government Regulation has a higher position than the Ministerial Regulation, this causes the making of the regulations below must refer to the regulations above so as not to collide/counter-productive. This rule collision will cause a legal gap if there is a lawsuit in the Administrative Court, so the product can be legally flawed and canceled. Kata Kunci : existence, announcement agency and PTSL Intisari: Pelaksanaan lembaga pengumuman sesuai PP No. 24 Tahun 1997 dan Pendaftaran Tanah Sistematik Lengkap (PTSL) terdapat perbedaan baik dalam jumlah hari pelaksanaan maupun status bidang tanah yang didaftarkan. Penelitian ini menggunakan metode penelitian hukum normatif dan hukum yuridis empiris yang bertujuan untuk mengetahui eksistensi lembaga pengumuman dalam pelaksanaan PTSL dan mengetahui konsekuensinya terhadap legalitas sertipikat hak atas tanah. Hasil dari penelitian ini adalah eksistensi lembaga pengumuman dalam PP No. 24 Tahun 1997 berbeda dengan pelaksanaan dalam PTSL. Secara tegas dalam PP No. 24 Tahun 1997 pengumuman hanya dilaksanakan untuk tanah adat selama 30 hari dan untuk tanah tanah negara tidak dilaksanakan pengumuman, sedangkan eksistensi lembaga pengumuman dalam PTSL tidak membedakan status tanah, baik itu tanah negara maupun tanah adat tetap dilakukan pengumuman selama 14 hari kalender. Sesuai dengan hierarki peraturan perundang-undangan, peraturan pemerintah memiliki kedudukan lebih tinggi dari peraturan menteri, hal ini menyebabkan pembuatan peraturan yang di bawah harus merujuk kepada peraturan yang ada di atasnya supaya tidak bertabrakan/kontra produktif. Tabrakan aturan ini akan menimbulkan celah hukum apabila terjadinya suatu gugatan di PTUN, sehingga produk yang dihasilkan bisa jadi cacat hukum dan dibatalkan. Kata Kunci : eksistensi, lembaga pengumuman dan PTSL